New feminist Christianity : many voices, many views - Hunt, Mary E., 1951-; Neu, Diann L., 1948- (Woodstock, Vt. : SkyLight Paths Pub., 2010)
A collection of essays by proclaimed feminist Christians, discussing their accomplishments and examining the lasting problems that hinder women's participation in the Christian community.
Cofounders of the Women's Alliance for Theology, Ethics and Ritual (water).
Includes bibliographical references (p. 296-328) and index.
Keywords: Feminist theology; Feminism -- Religious aspects -- Christianity